The wonder and angst of exploring the unknown: Introduction to the special issue on intolerance of uncertainty - McEvoy, Peter; Carleton, R. (Pergamon, 2016)
Interest in the relationship between intolerance of uncertainty (IU) and emotional disorders has rapidly increased over the last decade. Early theory and research focused on the relationship between IU and generalized anxiety disorder in particular; but, the roles that IU and the underlying 'fear of the unknown' play in the development, maintenance, and treatment of a broad array of emotional disorders have been explored more recently. This introduction provides a brief overview of the contributions to the special issue, which (a) summarize our current state of knowledge, (b) describe innovative methods for assessing and increasing our understanding IU within the context of various emotions and emotional disorders, (c) investigate associations between IU and therapeutic change, and (d) propose future research directions.